2020
DOI: 10.1038/s42003-020-01213-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of fish oil exacerbates alcoholic liver disease by enhancing intestinal dysbiosis in mice

Abstract: The role of n-3 polyunsaturated fatty acids (PUFAs) in alcoholic liver disease (ALD) has been controversial. N-3 PUFA oxidation in animal feeding stuffs was rarely concerned, likely contributing to inconsistent outcomes. Here, we report the impacts of oxidized fish oil (OFO) on ALD in C57BL/6 mice. Alcohol exposure increased plasma aminotransferase levels and hepatic inflammation. These deleterious effects were ameliorated by unoxidized FO but exacerbated by OFO. Sequencing analysis showed the accentuated inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…IL-1β level in the cell culture medium was measured using Human ELISA Standard kits according to the manufacturer’s instruction (Cloud-Clone, Wuhan, China). H&E staining was conducted to determine the histological changes of the liver as previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…IL-1β level in the cell culture medium was measured using Human ELISA Standard kits according to the manufacturer’s instruction (Cloud-Clone, Wuhan, China). H&E staining was conducted to determine the histological changes of the liver as previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dietary addition of omega-3 PUFAs increases the abundance and percentage of Bifidobacteria in the gut of male Sprague-Dawley rats [ 19 ]. EPA and DHA treatment could prevent gut microbiota dysregulation in mice [ 20 ] and increase the number of potentially beneficial lactic acid-producing bacteria and Bifidobacteria in the gut of the mice fed a high-fat diet [ 21 , 22 ]. Omega-3 PUFAs alter the abundance of beneficial intestinal bacteria, particularly Akkermansia , improve the intestinal microenvironment, increase the intestinal mucosal thickness, improve the barrier function of the intestinal mucosa, and achieve weight loss by controlling the expression of genes related to fat metabolism [ 23 ].…”
Section: Omega-3 Pufas and The Gut Microbiotamentioning
confidence: 99%
“…Research has shown that oxidized diets enhance plasma inflammatory markers and activate nuclear factor kappa B ( NF-κB ) in the small intestine, and consumption of oxidized n-3 PUFA results in 4-HHE accumulation in blood after its intestinal absorption and triggers oxidative stress and inflammation in the upper intestine ( Awada et al, 2012 ). A recent study showed that oxidized fish oil could cause intestinal dysbiosis, barrier dysfunction, and hepatic inflammation mediated by gut-derived endotoxin ( Feng et al, 2020 ). Importantly, induction of oxidative stress can be associated with intestinal inflammation and changes in host microbiota.…”
Section: Introductionmentioning
confidence: 99%